Decorrelation in Feedback Delay Networks - Schlecht, Sebastian J.; Fagerstrom, Jon; Valimaki, Vesa (IEEE/ACM Transactions on Audio, Speech and Language Processing, 2023)
The feedback delay network (FDN) is a popular filter structure to generate artificial spatial reverberation. A common requirement for multichannel late reverberation is that the output signals are well decorrelated, as too high a correlation can lead to poor reproduction of source image and uncontrolled coloration. This article presents the analysis of multichannel correlation induced by FDNs. It is shown that the correlation depends primarily on the feedforward paths, while the long reverberation tail produced by the recursive path does not contribute to the inter-channel correlation. The impact of the feedback matrix type, size, and delays on the inter-channel correlation is demonstrated. The results show that small FDNs with a few feedback channels tend to have a high inter-channel correlation, and that the use of a filter feedback matrix significantly improves the decorrelation, often leading to the lowest inter-channel correlation among the tested cases. The learnings of this work support the practical design of multichannel artificial reverberators for immersive audio applications.
CRIS-Team Scopus Importer:2023-11-06
Keywords: Correlation; Correlation; Decorrelation; Delay lines; Delays; Digital filters; digital filters; feedback circuits; MIMO communication; reverberation; Reverberation; spatial audio; spatial filters